Diversity, distribution and biology of Romanian flat-footed flies (Diptera, Opetiidae and Platypezidae) with taxonomic notes on Callomyia saibhira Chandler - Michal Tkoc; Jindřich Roháček (ZooKeys, 2014)
Altogether 18 species of the families Opetiidae and Platypezidae are reported from Romania, based on newly studied material and previously published records. The following three species are recorded from Romania for the first time: Agathomyia vernalis Shatalkin, 1981, Callomyia saibhira Chandler, 1976, and Lindneromyia hungarica Chandler, 2001. The presented differential diagnosis and a detailed redescription of body and genitalia of the male of Callomyia saibhira are based on one specimen which is the first male found in Europe. Information about distribution and biology of all 18 Romanian species is provided as well as photographs of selected important species. Finally, a new checklist of all Romanian species is given.